The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s11573-020-01009-6
|View full text |Cite
|
Sign up to set email alerts
|

Properties of feedback mechanisms on digital platforms: an exploratory study

Abstract: Many digital platforms implement feedback mechanisms as a means to control the behavior of their users. However, there is a lack of theoretical explanation regarding the interrelation between design characteristics of feedback mechanisms and their effects. In this study, we interpret feedback mechanisms as a specific type of management control to propose properties as a new theoretical perspective on this problem. Our exploratory study has two objectives. First, we analyze how digital platforms design their fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 96 publications
(218 reference statements)
0
3
0
Order By: Relevance
“…However, these governance mechanisms currently represent only examples in which a particular activity can be implemented and should be elaborated in further studies. E.g, Steur and Seiter ( 2021 ) have looked at how over 100 feedback mechanisms are implemented and summarized them in a complete design catalogue. Such an approach can be used for many of the mechanisms illustrated here.…”
Section: Discussionmentioning
confidence: 99%
“…However, these governance mechanisms currently represent only examples in which a particular activity can be implemented and should be elaborated in further studies. E.g, Steur and Seiter ( 2021 ) have looked at how over 100 feedback mechanisms are implemented and summarized them in a complete design catalogue. Such an approach can be used for many of the mechanisms illustrated here.…”
Section: Discussionmentioning
confidence: 99%
“…If the platform has a rating system for complements, the absolute number of complements that have a better average rating than a certain threshold can be another pervasive indicator to support complementarity (Steur and Seiter 2020). However, depending on the individual use case, this KPI cannot always be monitored in a reasonable way.…”
Section: Complementaritymentioning
confidence: 99%
“…They also give an overview of other existing approaches for gathering user feedback on accessibility barriers and discuss how the PBT can be used as a tool for gathering data to support effective implementation of the WAD at large, in addition to its function for users to give feedback on a particular issue. Steur and Seiter [8] studied the design of feedback mechanisms of more than 102 popular digital platforms and discussed design choices in the light of management control literature. They found that simplicity in the provision of feedback is essential but do not mention accessibility for people with impairments.…”
Section: Related Workmentioning
confidence: 99%